Pro Drupal 7 for Windows Developers - Travis, Brian; SpringerLink (Online service) (Berkeley, CA : Apress, 2011)
Drupal 7 opens the door for you as a Windows developer to build Drupal sites$1 (Bincluding custom modules$1 (Ball without leaving Visual Studio! Pro Drupal 7 for Windows Developers gives you everything you need to know to achieve this, whilst drilling down into the advanced topics that you'll want to master whilst working with Drupal 7 as a Windows developer. Pro Drupal 7 for Windows Developers starts with the Drupal page model, which Windows programmers can contrast against the ASP.NET page model. You will then explore the various features of Drupal, including the hook model, theming, roles, and caching. You'll also discover the data abstraction layer which lays the foundation for integration with your enterprise-level databases and external systems. Pro Drupal 7 for Windows Developers focuses on the important topics for the programmer coming to Drupal: An up-to-speed introduction to Drupal for developers so that they can get past the initial learning curve most efficiently. Key introductions to the important features of Drupal, including the page model, the hook architecture, the theming layer, and custom module development. How to work with the Drupal 7 features you want to work with within the Windows development environment. Step-by-step tutorials on building, testing, and deploying custom modules for internal use or for sharing with the Drupal community. Pro Drupal 7 for Windows Developers provides a bridge to Drupal for you as a Windows developer$1 (Bby speaking your language!s
Keywords: Computer science; Computer Science; Computer Science, general